2022
DOI: 10.1111/eje.12751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision‐making in complex endodontic cases between postgraduate students across dental specialties at a UK dental school: A pilot study

Abstract: Introduction Treatment decisions for a heavily restored endodontically treated tooth vary amongst clinicians owing to multitude of factors. This phenomenon not only often poses dilemmas to clinicians of different clinical backgrounds, but also exerts a degree of treatment difficulty to the treating clinician. Previous studies indicated that specialty training and clinical experience significantly impacted clinical decision‐making process. Materials and methods Master of Science postgraduate students in endodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Four studies found that the type of treatment had effects on confidence in clinical decision making [ 23 , 24 , 36 , 41 ]. Procedural predictability, technical difficulty and risk of iatrogenic damage influenced the clinician’s confidence in decision making [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies found that the type of treatment had effects on confidence in clinical decision making [ 23 , 24 , 36 , 41 ]. Procedural predictability, technical difficulty and risk of iatrogenic damage influenced the clinician’s confidence in decision making [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found that the type of treatment had effects on confidence in clinical decision making [ 23 , 24 , 36 , 41 ]. Procedural predictability, technical difficulty and risk of iatrogenic damage influenced the clinician’s confidence in decision making [ 36 ]. McGeown et al adds that equipment limits and time and facilities also played a role, while Fu et al considered timing of clinical findings as important for confidence in treatment planning, where late detection of tooth eruption disturbances can lead to greater complexity [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 This study also revealed that different outreach dental teams uate training in various specialities, on the treatment decisions for complex endodontic cases reported that procedural predictability, technical difficulty, risk of damage to the tooth and patient preference were the most important factors affecting clinical decisionmaking. 23 The authors suggested that evidence-based treatment guidelines and dental curricula should be reviewed to enhance interclinician agreement in clinical decision-making. These guidelines should also be available for the patients and their caregivers and they should be included in the clinical decision-making process to enhance patient care and cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, postgraduate endodontic education is an advanced level of endodontic knowledge and skills. It allows students to apply their knowledge and skills in a real patient setting under the guidance of experienced clinicians, aiming to cultivate high‐quality professionals with a solid theoretical foundation, 3 outstanding technical skills, 4 and the ability to think critically and conquer complex problems in a clinical context 5 . Such education requires a commitment to professional growth, as well as a continuous drive to innovate and advance through practical research.…”
Section: Introductionmentioning
confidence: 99%